2019
DOI: 10.1523/jneurosci.2969-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role for Human Ventromedial Frontal Lobe in Value Comparison of Complex Objects Based on Attribute Configuration

Abstract: In making decisions, we often choose from among options with multiple value-relevant attributes. Neuroeconomic models propose that the value associated with each attribute is integrated in a global value for each option. However, some evidence from patients with ventromedial frontal lobe (VMF) damage argues against a very general role for this region in value integration, suggesting instead that it contributes critically to a specific value inference or comparison process. Here, we tested value-based decision-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
39
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 42 publications
7
39
0
Order By: Relevance
“…Further evidence supports attribute-based computations in prefrontal cortex (PFC), such as the distinction between whether a food is judged to be tasty or healthy, 19 or even in judgments about the value of clothing, 20 as well as the value of multi-attribute artificial stimuli (e.g., the movement and the color of dots) in humans and macaques. [21][22][23] However, it is not clear if the same feature-based strategy used by the brain to derive value for items suited to a functional decomposition 24 is also applied when performing the rather esoteric function of determining the aesthetic value of visual art. In previous work on feature integration, the features are natural and obvious properties of a stimulus such as a food's fat content.…”
Section: Introductionmentioning
confidence: 99%
“…Further evidence supports attribute-based computations in prefrontal cortex (PFC), such as the distinction between whether a food is judged to be tasty or healthy, 19 or even in judgments about the value of clothing, 20 as well as the value of multi-attribute artificial stimuli (e.g., the movement and the color of dots) in humans and macaques. [21][22][23] However, it is not clear if the same feature-based strategy used by the brain to derive value for items suited to a functional decomposition 24 is also applied when performing the rather esoteric function of determining the aesthetic value of visual art. In previous work on feature integration, the features are natural and obvious properties of a stimulus such as a food's fat content.…”
Section: Introductionmentioning
confidence: 99%
“…They found that distinct areas were independently specific for each attribute, and that a third area showed activity correlated with the combined signals from the earlier areas. The importance of later-areas for the integration of value signals was demonstrated by (Pelletier and Fellows 2019) in patients with damage to the OFC and vmPFC. They found that these patients were able to make decisions based on single attributes (the form of elements in an object versus the configuration of elements) no different from controls.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, BMI was negatively related to the gray matter (GM) volume in the right lateral and medial orbitofrontal cortex (Medic et al, 2016;Vainik et al, 2018). Neuropsychological studies with brain lesioned patients have reported that lesions in the ventromedial prefrontal cortex lead to deficits in the integration of information (Pelletier and Fellows, 2019) and that lesions in the right ventrolateral cortex lead to problems in inhibitory control (Aron et al, 2004). Thus, these BMI results reinforce the idea of deficits in executive functions and inhibitory control as mechanisms leading to overweight at an early age (Alonso-Alonso and Pascual-Leone, 2007).…”
Section: Introductionmentioning
confidence: 99%